Analisis Kepuasan Peserta Didik dalam Pembelajaran Jarak Jauh di Masa Pandemi Covid–19 - Ilmadi; Sastro, Gerry; Saefullah, Rifki; Nirmala Sari, Deka; Wijaya, Deni (PUSAT SAINS INDONESIA, 2021)
Mater Dei School provides education from an early age to high school, currently Mater Dei school is in great demand by students because of its superior achievements, especially in the academic field. At the junior high school level, Mater dei has a total of 496 students. This study aims to determine, namely: 1) How is the level of student satisfaction with the quality of services provided by SMP Mater Dei Pamulang, South Tangerang City, 2) What factors need to be improved by SMP Mater Dei Pamulang, South Tangerang City in order to improve service quality, 3) Knowing how the proposed improvements are prioritized for improving the quality of services at SMP Mater Dei Pamulang, South Tangerang City. The study took data of 100 respondents, then performed serqual calculations to determine the value of GAP, the results of the GAP were used as input data for Importance Performance Analysis (IPA) which then identified 6 attributes that must be considered and need to be considered by management to improve service quality. The next step is to calculate the Costomer Satisfaction Index (CSI). From the results of the analysis, the value was 79.125%. This means that the level of student satisfaction with SMP Mater Dei services is in the Satisfied category. Furthermore, the 6 attributes in question need to be recommended to managers to improve their services so that the service satisfaction value becomes 100%.